Antioxidant Activity Etanolic Extract from White Mangrove Leaf (Avicennia marina) by FRAP (Ferric Reducing Antioxidant Power) Method - Nurany, Asfy; Haryoto, H (Universitas Muhammadiyah Surakarta, 2019)
White mangrove (Avicennia marina) is one type of mangrove that has potential as a natural antioxidant. Antioxidants are compounds that can eliminate and withstand the effects of negative reactions from free radicals. This aim study to determine the antioxidants of the ethanolic extracts of the mangrove leaves of white mangrove by using the FRAP (Ferric Reducing Antioxidant Power) method. White mangrove leaves (Avicennia marina) were extracted by maceration with 96% ethanol solvent. Then fractionation was carried out, resulting in three fractions : n-hexane, ethyl acetate and ethanol. These three fractions were then tested for antioxidant activity using the FRAP (Ferric Reducing Antioxidant Power) method. This method use a UV-Vis spectrophotometer with a wavelength of 720 nm and the total value of antioxidant activity is calculated based on the absorbance of the data obtained. Based on the calculation results show that ethanol extract, hexane fraction, ethyl acetate and ethanol of white mangrove leaves (Avicennia marina) have antioxidant activity respectively 2.7906; 2.71808; 2.78178 and 2.7854 mgAAE/g extract.